2000
DOI: 10.1046/j.1524-4725.2000.00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete Spontaneous Regression of Merkel Cell Carcinoma: A Review of the 10 Reported Cases

Abstract: While only 10 cases of CSR is a small number, MCC is itself a rare malignancy with just over 600 reported cases. Today most cases of MCC receive aggressive combined therapy effectively precluding diagnosis of CSR. The nature of regression in these 10 cases may point toward future immunologic therapy just as similar cases of CRS in patients with melanoma have led to advances in the immunologic treatment for that malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(41 citation statements)
references
References 18 publications
(23 reference statements)
0
39
0
1
Order By: Relevance
“…Regression of cutaneous Merkel cell carcinoma and nodal metastasis has rarely been reported, mostly after either surgical excision or needle biopsy of the primary lesion; and it was thought to be due to the procedures, which stimulated cell-mediated immune clearance of the residual tumor cells. [36][37][38][39][40][41][42][43][44] It is difficult to envision the spontaneous resolution of cutaneous Merkel cell carcinoma without prior medical intervention in all of our cases; moreover, it is very unlikely that all the primary tumors would have regressed without leaving any visible remnants. Therefore, we speculate that some of our nodal cases may represent primary nodal neoplasms.…”
Section: Possible Histogenesis Of Nodal Merkel Cell Carcinomamentioning
confidence: 99%
“…Regression of cutaneous Merkel cell carcinoma and nodal metastasis has rarely been reported, mostly after either surgical excision or needle biopsy of the primary lesion; and it was thought to be due to the procedures, which stimulated cell-mediated immune clearance of the residual tumor cells. [36][37][38][39][40][41][42][43][44] It is difficult to envision the spontaneous resolution of cutaneous Merkel cell carcinoma without prior medical intervention in all of our cases; moreover, it is very unlikely that all the primary tumors would have regressed without leaving any visible remnants. Therefore, we speculate that some of our nodal cases may represent primary nodal neoplasms.…”
Section: Possible Histogenesis Of Nodal Merkel Cell Carcinomamentioning
confidence: 99%
“…20,33 Spontaneous regression of cutaneous MCC has been described. [35][36][37][38] In 10% to 20% of patients with metastatic MCC, the primary tumor is not identified. Differentiating MCC from primary Merkel cell-like small cell carcinoma of the salivary gland in this scenario can be almost impossible.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…24 Spontaneous regression has been noted in some patients with MCC. [35][36][37][38] Apoptosis and T-cell immune response involvement has been suggested as the mechanism behind tumor regression. 37 In conclusion, the incidence of MCC is rising: It is diagnosed most commonly in elderly or immunocompromised patients, and it has higher mortality than melanoma.…”
Section: Staging and Treatmentmentioning
confidence: 99%
“…Even though the general nature of the tumor is rapid growth and early metastases, there are published data on spontaneous regression 49 . Mori et al 50 observed high apopoptic tumor activity in 8 cases of patients treated for MCC.…”
Section: Discusionmentioning
confidence: 99%